PELATIHAN LITERASI KEUANGAN UNTUK KESADARAN FINANSIAL SISWA SMA NEGERI 1 WONOSARI - Yohanes Mario Pratama; Elizabeth Fiesta Clara Shinta Budiyono; Raymundo Patria Hayu Sasmita (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The community service activity aims to enhance financial literacy and financial awareness among eleventh-grade students of SMA Negeri 1 Wonosari through a structured and contextual financial literacy training program. The activity was conducted using interactive lectures, case discussions, classroom dialogues, and student reflections on daily financial habits. The training materials covered basic financial literacy concepts, financial levels, spending quadrants, and financial intelligence. The results indicate that the program improved students’ understanding of personal financial management, the ability to distinguish between needs and wants, and awareness of the consequences of financial decisions. Students also demonstrated initial awareness of managing their allowance more wisely by planning expenditures and considering simple financial planning practices. These findings suggest that financial literacy training at the secondary school level plays a crucial role in establishing an early foundation for responsible financial behavior and long-term financial readiness.